Employability in Adult and Higher Education. Issue 163 (3rd September 2019) - Boffo, Vanna; Melacarne, Claudio
Abstract: The chapters contained in this special issue are summarized here, highlighting core themes and future implications for research and practice for adult education and lifelong learning.